Vintage contemporaries : a novel - Kois, Dan (Harper, an imprint of HarperCollinsPublishers, 2023)
Pulled back into her past when a posthumous work needs a publisher, reconnecting her with an old friend, successful book editor and new mom Emily is forced to reckon with her decisions, her failures, and what kind of creative life she wants to lead.